The Influence of Intelligence and Achievement Motivation on Student Learning Achievement at SMAN 16 Gowa in Biringbulu District, Gowa Regency - Pahrul, Pahrul; Ansyari, Mas'ud Uqbah Al; Putrawan, Muh. Rizah; Wisudawaty, Ika (International Journal of Education, Vocational and Social Science, 2024)
The purpose of this study was to determine the effect of intelligence and achievement motivation on student learning achievement at SMAN 16 Gowa in Biringbulu District, Gowa Regency, where this study used a type of quantitative research, while the data collection method applied was through questionnaires distributed to 30 respondents with taken from students of SMAN 16 Gowa. Simultaneously the two variables (X) have a significant influence together on student achievement. However, based on the partial significant test, the Intelligence variable (X1) and Achievement Motivation (X2) do not have a significant effect on the Learning Achievement variable (Y).